The Impact of Using Picture Cards to Improve English Vocabulary Skills Among Kindergarten Students at TK Tunas Jaya - Epi Gustina Sari (Universitas Muhammadiyah Lampung, 2023)
Proficiency in English vocabulary constitutes a fundamental foundation for young learners, as it facilitates the development of listening, speaking, reading, and writing skills. Nevertheless, many children in kindergarten still encounter challenges in recognising, recalling, and comprehending basic English vocabulary due to limited exposure to engaging and developmentally appropriate educational media. This study aims to investigate the influence of picture cards on enhancing English vocabulary mastery among children in Group B at TK Tunas Jaya. The research employed a quantitative methodology with a one-group pretest–posttest design, involving twenty children as participants. Data were gathered through vocabulary assessments administered before and after the intervention. The intervention comprised four instructional sessions utilising picture cards centred on themes such as colours, animals, fruits, and classroom objects. The strategies implemented included show and say, memory games, and flashcard drills, all designed to increase children’s engagement and memory recall capabilities.